The ERP process system as a direction of the evolution of integrated management information systems - Turek, Tomasz; Dziembek, Damian (Procesowy system ERP jako kierunek ewolucji zintegrowanych systemów informatycznych zarządzania, 2018)
The article attempts to indicate the direction of ERP class information systems development. From the beginning, these systems have been changing and evolving. Along with the development of requirements and changes on the market, solutions known as ERP II and ERP III were created. Currently, these systems use a process approach. Three basic types of systems can be distinguished: ERP systems supporting processes, process-oriented ERP systems and process ERP systems. The considerations in the article are based on the Macrologic Merit ERP system, which not only supports processes, has a built-in modeler but also allows full service of processes in the system. The applied approach allows for the effective process management, analysis and improvement
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 3 (49), s. 118-131
Keywords: ERP; process oriented ERP; management information systems; procesowe systemy ERP; systemy informatyczne zarządzania